PERUBAHAN TINGKAT SUKU BUNGA DAN KINERJA PASAR MODAL INDONESIA: ANALISIS PADA TINGKAT PASAR DAN TINGKAT INSUTRI - I Wayan Nuka Lantara (UGM, 2004)
The objective of this paper is to test empirically the performance of Indonesia capital market following the interst rate change. This study also test the ralationship between the interst rate changes and the subsequence performance in various industries, which are financial and manufacture sectore. We used level analysis as industry level analysis.